Shared reading quality assessment by parental report: preliminary validation of the DialogPR - John S Hutton; Guixia Huang; Kieran J Phelan; Thomas DeWitt; Richard F Ittenbach (BMC, 2018)
Abstract Background The American Academy of Pediatrics (AAP) recommends shared reading beginning as soon as possible after birth to promote healthy development. Shared reading quality can strongly influence outcomes, especially in children from low-SES households. Dialogic reading is a method developed to enhance verbal interactivity and engagement through book sharing, advocated by the AAP and clinic-based programs such as Reach Out and Read. There is no brief, validated, caregiver report measure of dialogic reading or shared reading quality currently available. Methods This cross-sectional study involved 49 healthy mother-child dyads (mean child age 4.5 yrs., SD = 0.6 yrs.) from 2 separate MRI-based studies. The DialogPR was administered by trained research coordinators following MRI, along with the READ subscale of the validated StimQ-P measure of home cognitive environment. The DialogPR consists of eight items developed in consultation with experts in early literacy, based on the PEER/CROWD dialogic reading conceptual model. Estimated reading level is 6th grade. Descriptive statistics were computed at both the item and scale levels. Modern theory Rasch methods were used to analyze all eight DialogPR items along with preliminary estimates of reliability and validity. Results Our combined sample involved 15 boys and 34 girls, and was diverse in terms of age, household income, and maternal education. DialogPR administration time was less than 2 min, with no problems reported. The DialogPR demonstrated strong internal consistency and reliability (Cronbach's alpha = 0.82), and criterion-related validity with the StimQ-P READ (Spearman's rho coefficient = 0.53). Rasch analysis revealed strong psychometric properties in terms of reliability, variability in item difficulty, and inter-item and item-measure correlations. Conclusions Preliminary evidence suggests that the DialogPR may be an efficient means to assess shared reading quality and dialogic reading via caregiver report for clinical and research purposes, warranting further investigation.